Challenges In The Diagnosis And Management Of A Ruptured Heterotopic Gestation Following Ultrasound-Guided Embryo Transfer In Low Resource Settings: A Case Report - Oyeh, E.; Ofori, S.; Sefogah, P.E.; Hiadzi, E.K. (Journal of Medical Case Reports, 2024)
Background Heterotopic pregnancies are increasing in incidence with the rising prevalence of in vitro fertilization and embryo transfer (IVF-ET) globally. Although rare, this condition is serious and potentially life-threatening gynaecological complication. Case presentation We present the case of a 36-year-old Ghanaian woman who conceived following IVF and presented two weeks after confrmation of intrauterine gestation with sudden-onset lower abdominal pain. A diagnosis of ruptured heterotopic pregnancy was made, laparotomy and salpingectomy were done, followed by further management of the intrauterine gestation. Conclusion To the best of our knowledge, this is the first reported case of heterotopic pregnancy in Ghana. A high index of suspicion for heterotopic pregnancy is required even in the presence of a confirmed intrauterine gestation following IVF-ET.
Research Article
Keywords: Heterotopic pregnancy; In vitro fertilization and embryo transfer; Salpingectomy